1973
DOI: 10.1136/gut.14.6.502
|View full text |Cite
|
Sign up to set email alerts
|

The significance of enzyme histochemical patterns in carcinomas of the large intestine in man

Abstract: SUMMARY The activities of 13 enzymes in 40 carcinomas of the large bowel have been studied using histochemical techniques. Five enzymes-non-specific esterase, monoamine oxidase, succinate dehydrogenase, cytochrome oxidase, and acid phosphatase-commonly show much less activity in the tumours than in adjacent normal colon. The tumours have been classified based upon the number of enzymes which show marked reduction in activity in each tumour (types 1-5). The enzyme histochemical type and the size of the tumours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
3

Year Published

1974
1974
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…Also, the present results revealed an increase in the level of LDH enzyme in toads treated with the chemical carcinogen (DMBA), while its activity was decreased in significantly after treatment with indomethacin. Also, it has been shown that the activity of LDH was increased in men colon cancer (McGinty et al, 1973). However, the decrease in LDH enzyme was observed after the effect of antitumor drug (5-Flurouracil) in colon adenocarcinoma (Ismail et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the present results revealed an increase in the level of LDH enzyme in toads treated with the chemical carcinogen (DMBA), while its activity was decreased in significantly after treatment with indomethacin. Also, it has been shown that the activity of LDH was increased in men colon cancer (McGinty et al, 1973). However, the decrease in LDH enzyme was observed after the effect of antitumor drug (5-Flurouracil) in colon adenocarcinoma (Ismail et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…(1973) hier eine negative Reaktion fest. Ein negativer Befund wird zunächst auch beim Menschen erhoben (Dawson und Pryse‐Davies, 1963; Filipe, 1971; McGinty et al., 1973). In jüngerer Zeit demonstrieren jedoch Bell und Williams (1979) histochemisch und Benjawatanapon et al.…”
Section: Diskussionunclassified
“…WaÈ hrend Helander (1975) eine sehr geringe AktivitaÈ t der alkalischen Phosphatase in den Dickdarmepithelien der Ratte beobachtet, stellen Masnerova et al (1966) sowie HoÈ hn et al (1973 hier eine negative Reaktion fest. Ein negativer Befund wird zunaÈ chst auch beim Menschen erhoben (Dawson und Pryse-Davies, 1963;Filipe, 1971;McGinty et al, 1973). In juÈ ngerer Zeit demonstrieren jedoch Bell und Williams (1979) histochemisch und Benjawatanapon et al (1982) feinstrukturell AktivitaÈ ten einer von Williams (1977) biochemisch nachgewiesenen, hitzelabilen alkalischen Phosphatase im menschlichen Dickdarmepithel.…”
unclassified